Applying design pattern to the development of library book management system / Muhammad Haidhir Derani - Derani, Muhammad Haidhir (2017)
Merlimau Public Library is an organization that provides free knowledge as well as services for public use. This project focuses on the processes of managing books within the public Library. While in the library the computerized system already exist, an improvement need to be made as more data can be stored in more systematized way. A Design Pattern is used to design the new system as it allows easy maintenance and evolution of the system. A waterfall methodology that is based on System Development Life Cycle (SDLC) is used to develop the system. Only three phases from the core processes is utilised which are Requirement Gatherings and Analysis, Design, and Implementation. Knowledge Acquisition phase is added as a part of the first phase in order to understand about the focus of this project which is the Design Pattern. There are 6 use cases and 7 class identified. The detail design classes were identified from domain class diagram and built following the selected Design Pattern which is MVC pattern. The Multilayer Sequence Diagrams, System Architecture, and Package Diagram are also created linearly in order to develop a new improved system for Merlimau Public Library. In the near future, the system should be available and integrated with mobile application system as features for patrons of the library can be implemented, since people nowadays tend to use the smartphone rather than the Web in order handle their matter.